Plant volatile eliciting FACs in lepidopteran caterpillars, fruit flies, and crickets: a convergent evolution or phylogenetic inheritance? - Yoshinaga, Naoko; Abe, Hiroaki; Morita, Sayo; Yoshida, Tetsuya; Aboshi, Takako; Fukui, Masao; Tumlinson, James H.; Mori, Naoki (Frontiers in Physiology, 2014)
Fatty acid amino acid conjugates (FACs), first identified in lepidopteran caterpillar spit as elicitors of plant volatile emission, also have been reported as major components in gut tracts of Drosophila melanogaster and cricket Teleogryllus taiwanemma. The profile of FAC analogs in these two insects was similar to that of tobacco hornworm Manduca sexta, showing glutamic acid conjugates predominantly over glutamine conjugates. The physiological function of FACs is presumably to enhance nitrogen assimilation in Spodoptera litura larvae, but in other insects it is totally unknown. Whether these insects share a common synthetic mechanism of FACs is also unclear. In this study, the biosynthesis of FACs was examined in vitro in five lepidopteran species (M. sexta, Cephonodes hylas, silkworm, S. litura, and Mythimna separata), fruit fly larvae and T. taiwanemma. The fresh midgut tissues of all of the tested insects showed the ability to synthesize glutamine conjugates in vitro when incubated with glutamine and sodium linolenate. Such direct conjugation was also observed for glutamic acid conjugates in all the insects but the product amount was very small and did not reflect the in vivo FAC patterns in each species. In fruit fly larvae, the predominance of glutamic acid conjugates could be explained by a shortage of substrate glutamine in midgut tissues, and in M. sexta, a rapid hydrolysis of glutamine conjugates has been reported. In crickets, we found an additional unique biosynthetic pathway for glutamic acid conjugates. T. taiwanemma converted glutamine conjugates to glutamic acid conjugates by deaminating the side chain of the glutamine moiety. Considering these findings together with previous results, a possibility that FACs in these insects are results of convergent evolution can not be ruled out, but it is more likely that the ancestral insects had the glutamine conjugates and crickets and other insects developed glutamic acid conjugates in a different way.